N6-methyladenosine (m6A) reader IGF2BP1 facilitates clear-cell renal cell carcinoma aerobic glycolysis - Bao Yuan; Jin Zhou (PeerJ, 2023)
Emerging articles have reported that N6-methyladenosine (m6A) modification is mainly involved in clear-cell renal cell carcinoma (ccRCC) tumorigenesis. However, the regulatory mechanisms of m6A reader IGF2BP1 involved in ccRCC tumor energy metabolism are currently unknown. Results showed that the m6A reader IGF2BP1 exhibited significantly higher expression in ccRCC cells. Functionally, results by gain/loss functional assays indicated that IGF2BP1 promoted the glycolytic characteristics, including glucose uptake, lactate production and extracellular acidification rate (ECAR). Mechanistically, IGF2BP1 recognized the m6A modified sites on LDHA mRNA and enhanced its mRNA stability, thereby accelerating tumor energy metabolism. Thus, our work reveals a novel facet of the m6A that promoted mRNA stability and highlighted the functional importance of IGF2BP1 as m6A readers in post-transcriptional gene regulation.